Knowledge Management Systems in Higher Education: A Comprehensive Study through Systematic Literature Review and Bibliometric Analysis (2019-2023) - Faldesiani, Riske; Senen, Syamsul Hadi (Eastasouth Institute, 2024)
The objective of this study is to critically examine the existing body of literature on Knowledge Management Systems (KMS) in the context of higher education. The research employed the PRISMA technique (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) together with a bibliometric approach and computational mapping analysis utilizing VOS Viewer. The study period used as literature data material is Scopus-indexed articles and conference papers from 2019 to 2023. The keywords used were